2017
DOI: 10.3389/fphys.2017.00367
|View full text |Cite
|
Sign up to set email alerts
|

Extraction Protocols for Individual Zebrafish's Ventricle Myosin and Skeletal Muscle Actin for In vitro Motility Assays

Abstract: The in vitro motility assay (IVMA) is a technique that enables the measurement of the interaction between actin and myosin providing a relatively simple model to understand the mechanical muscle function. For actin-myosin IVMA, myosin is immobilized in a measurement chamber, where it converts chemical energy provided by ATP hydrolysis into mechanical energy. The result is the movement of fluorescently labeled actin filaments that can be recorded microscopically and analyzed quantitatively. Resulting sliding sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Recently, Scheid et al ( 2017 ) purified zebrafish skeletal muscle actins and demonstrated their filament forming and myosin interacting capacities in vitro. Despite a lack of data regarding the biochemical properties of zebrafish cytoplasmic actins, considering the fact that they share almost complete sequence homology with the well-studied mammalian actins, it is likely that their properties and structure are similar to the mammalian proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Scheid et al ( 2017 ) purified zebrafish skeletal muscle actins and demonstrated their filament forming and myosin interacting capacities in vitro. Despite a lack of data regarding the biochemical properties of zebrafish cytoplasmic actins, considering the fact that they share almost complete sequence homology with the well-studied mammalian actins, it is likely that their properties and structure are similar to the mammalian proteins.…”
Section: Introductionmentioning
confidence: 99%
“…It has recently been shown that the IVMA time scale of actin-myosin interaction (with, e.g., myosin II motor protein cycle times in the range of 150 ms) is mainly determined by the myosin functioning as an ensemble (Rastogi et al, 2016). The assay is performed in a large number of variations using proteins from different animals (Höök et al, 1999; Elangovan et al, 2012; Scheid et al, 2017). It can be used to selectively study myosin isoforms and actin mutants, and for drug screenings to find candidates for the treatment of skeletal and cardiac muscle diseases.…”
Section: Introductionmentioning
confidence: 99%